Pericardial effusion and mitral valve involvement in systemic lupus erythematosus. Echocardiographic study. Issue 4 (August 1977) - Elkayam, U; Weiss, S; Laniado, S
Abstract : Echocardiography was used in 30 women and 2 men with systemic lupus erythematosus (SLE) in order to determine the incidence and severity of pericardial effusion and mitral valve involvement. 31 patients showed normal thickness of the mitral valve leaflets, only one patient showed irregular thickening of the leaflets suggesting the presence of vegetations. Mitral valve motions were normal in all patients. These results indicate that myocardial and valvular involvement in SLE is usually not severe enough to result in haemodynamic abnormalities. Pericardial effusion was found in 2 patients who were symptom free, whereas 4 of the patients with a past history suggestive of pericarditis showed no echocardiographic evidence of pericardial effusion. These suggest the transient nature of pericarditis in SLE, and the value of echocardiography as a diagnostic tool in detecting clinically inapparent lupus pericarditis.